- #1

- 4

- 0

## Main Question or Discussion Point

Can anyone help me with this?

If gcd(r,s)=1 then prove that gcd(r^2-s^2, r^2+s^2)=1 or 2.

i'm so confused.

If gcd(r,s)=1 then prove that gcd(r^2-s^2, r^2+s^2)=1 or 2.

i'm so confused.

- Thread starter awesome220
- Start date

- #1

- 4

- 0

Can anyone help me with this?

If gcd(r,s)=1 then prove that gcd(r^2-s^2, r^2+s^2)=1 or 2.

i'm so confused.

If gcd(r,s)=1 then prove that gcd(r^2-s^2, r^2+s^2)=1 or 2.

i'm so confused.

- #2

CRGreathouse

Science Advisor

Homework Helper

- 2,820

- 0

Suppose [itex]n|(r^2-s^2)[/itex] and [itex]n|(r^2+s^2)[/itex]. (This would be the case for the gcd of the two expressions.) Then there are some integers a, b withCan anyone help me with this?

If gcd(r,s)=1 then prove that gcd(r^2-s^2, r^2+s^2)=1 or 2.

i'm so confused.

[tex]an=r^2-s^2[/tex] and [tex]bn=r^2+s^2[/tex].

Then [itex](a+b)n=2r^2[/itex] and so n divides [itex]2r^2[/itex]. Does this help?

- #3

- 4

- 0

I understand, but how does that give us that gcd (r^2-s^2, r^2+s^2) = 1 or 2?

- #4

- 4

- 0

nevermind, I think i see it! Thanks!

- Last Post

- Replies
- 5

- Views
- 3K

- Last Post

- Replies
- 6

- Views
- 2K

- Last Post

- Replies
- 2

- Views
- 2K

- Last Post

- Replies
- 2

- Views
- 4K

- Last Post

- Replies
- 3

- Views
- 2K

- Last Post

- Replies
- 59

- Views
- 11K

- Last Post

- Replies
- 11

- Views
- 3K

- Last Post

- Replies
- 15

- Views
- 8K